Tax Exemption through Letters: Issues of Legality and Equality - Tsegay, Ataklti Weldeabzgi (Bahir Dar University Journal of Law, 2022)
Employment income is one source of income tax in Ethiopia. Employees, in addition to their periodic salary, may be entitled to other payments or gains in cash or in kind during the employment relationship. The main concern of this article is to assess whether payments other than periodic salary of an employee, particularly house and transportation allowances, are taxable or not. The income tax proclamation, income tax regulation and income tax exemption directive provide employment incomes exempted from taxation. other institutions employees are not exempted. The acts of those institutions that request exemption of tax liability and the office thatrant exemption violate the income tax proclamation which imposes an obligation on them to cooperate in the enforcement of the proclamation. Particularly, ERCA, the principal body in the administration of tax, fails to respect and ensure compliance of tax laws. However, house and transportation allowances are not among those exempted. Practically, the writer traced that some federal government institutions, including Ethiopian Revenues and Custom Authority (ERCA) employeesâ€™ incomes received in the form of house and transportation allowances and one regional government institution employeesâ€™ income paid for house allowance are exempted from taxation via letters written by the Office of the Prime Minister and the regional government Supreme Court respectively. The exemptions for the federal government institutions employees are granted following the request of their employers. These exemptions being made by bodies not authorized by law to grant exemption and the means of exemption, i.e., the letters raise basic questions of legality. The exemptions also violate the principle of equality as similar incomes of other institutions employees are not exempted. The acts of those institutions that request exemption of tax liability and the office thatgrant exemption violate the income tax proclamation which imposes an obligation on them to cooperate in the enforcement of the proclamation. Particularly, ERCA, the principal body in the administration of tax, fails to respect and ensure compliance of tax laws.